1987
DOI: 10.1042/cs0730515
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis-associated amyloidosis: β2-microglobulin alone or associated with globin chains?

Abstract: 1. The protein constituents of amyloid fibrils were characterized in amyloid deposits extracted from surgical material obtained from a 66-year-old patient undergoing maintenance haemodialysis and operated for a carpal tunnel syndrome. 2. Sodium dodecyl sulphate/polyacrylamide-gel electrophoresis disclosed the presence of bands at 12 and 14 kDa. Two-dimensional electrophoresis and Western blotting confirmed that the proteins were beta 2-microglobulin (beta 2M) and globin chains. 3. When the effluent of high-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…2 -M), other compounds which could have been present at the start of the procedure might have been overlooked. We J. M. Campistol and A. Argiles found that this could have been the case for globin chains [35].…”
Section: Technical Approachmentioning
confidence: 76%
See 1 more Smart Citation
“…2 -M), other compounds which could have been present at the start of the procedure might have been overlooked. We J. M. Campistol and A. Argiles found that this could have been the case for globin chains [35].…”
Section: Technical Approachmentioning
confidence: 76%
“…We have identified the latter as being a 2 -macroglobulin [33]. We have also identified some of the remaining proteins found with TCA precipitation as being globin chains, light chains of immunoglobulins, and also albumin, haemopexin and transferrin [32,34,35]. The second aspect is the technical approach to analyse the protein solution after preparation.…”
Section: Technical Approachmentioning
confidence: 99%
“…In addition, high-molecular-mass peaks above the ovalbumin marker were detected in both the /2m and HLA assays, and therefore contained Class I-associated fi2m. In the sera from the haemodialysis patients, an additional fl2m fraction was observed in a region where no HLA was detected (fractions [24][25][26][27][28]. As this peak may represent free ,f2m molecules associated in a dimeric form, a further characterization of free thin forms in such patients was carried out by immunopurification of fl2m.…”
Section: Resultsmentioning
confidence: 99%
“…[27] and Argiles et al [28] have isolated and sequenced the acidic forms of monomeric fl2m isolated from dialysis fluid and serum respectively of haemodialysis patients. We demonstrate for the first time in this paper the presence of a circulating dimeric form of f82m.…”
Section: Discussionmentioning
confidence: 99%
“…Linke et al [70, 71]observed proteolyzed β 2 -microglobulin in amyloid material from dialysis patients. However, most of the reports that have analyzed the sequence of β 2 -microglobulin suggest that proteolysis is not necessary to form amyloid deposits [10, 72, 73, 74, 75]. Subsequently, other forms of amyloidosis have also been found to have an intact N terminus of their major protein: atrial natriuretic factor [76, 77], AL [78], and AA [79]amyloidosis.…”
Section: β2-microglobulin-related Factors:the Agep Hypothesismentioning
confidence: 99%